Determinan Keputusan Pembelian Produk Di Tokopedia: Promosi Event Free Photocard Dan Brand Ambassador - Wulandari, Wuri (Soratekno Publisher, 2024)
In the digital era, a unique phenomenon currently occurring is that Indonesian e-commerce is trying to attract Korean artists or celebrities to become brand ambassadors. This is motivated by the rise of the Korean wave in Indonesia. This research aims to determine the influence of the free photocard and brand ambassador event promotional variables on purchasing decisions for products on Tokopedia. This research uses a quantitative approach. The population in this study were Tokopedia consumers who had purchased products on Tokopedia during the Free Photocard Event promotion and knew BTS as the Tokopedia Brand Ambassador. The sample in this study was 100 respondents. The data collection technique used was a survey technique assisted by a questionnaire instrument with a Likert scale. The type of data used in this research is primary data. Data analysis techniques use Validity Test, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, F Test, T Test, and Coefficient of Determination Test. Based on the results of static data analysis, this research variable is valid and reliable, in the classical assumption test no multicollinearity and heteroscedasticity were found and it was normally distributed. The results of this research show that the independent variables Free Photocard Event Promotion and Brand Ambassador have a partial and significant effect on the dependent variable Purchase Decisions for products on Tokopedia. The independent variables Promotion of the Free Photocard Event and Brand Ambassador simultaneously and significantly influence the dependent variable on Purchase Decisions for products on Tokopedia.